(3ChbGa GdefRd aj LejY GdbQBf GdcQjes ((3CMeO QaYJ s)
(3ChdgG (B:s
(3ChbGa GdefRd ai LejY GdbQBf NeSI YTQ GdChd ai GdHbQI Nha Ydjge hdG ge jMRfhf Ke jHJOF GdPjf s
(3BNQgG (B:s
(3GdNGeS YTQ HSe Gddg GdQMef GdQMje Ke jHJOF CdgGce GdSGOS YTQ hgh RGFO Yf gPg GdLedI hgh CjVkG ai ShQI GdGYGQa Ydi ef jTGA Ke jHJOF eG XffJe Je Gdhba GdefRd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs